Do the foreign exchange reserves spur economic growth - ASSI, Brou Jean Ebenezer (KDI School, 2016)
The lessons drawn from the world financial crises have led to an increase in foreign exchange reserves worldwide. If many advanced economies have decided to take these steps to stay resilient to any financial crisis, the question remains on the opportunity cost that developing and most specifically African countries have to follow suit given their economic backwardness. This question will be answered in evaluating the impact that foreign exchange reserves of African countries have on their economic growth. This evaluation is done through a multiple linear regression model estimated with ordinary least squares method from a database that covers the period 1990-2014 for 30 African countries. We conclude that only 11 African countries have benefited from a positive return of their foreign exchange reserves on economic growth during this period while the other 19 have not. Furthermore, all other independent variables namely, domestic investment, foreign direct investment, Gross Domestic Product, international trade, exchange rate and inflation rate affect the economic growth of those countries in different proportions, their effect depending on the structure of the national economy. To play their game well, African economies as a rule should reduce their dependency from foreign financial aid and agricultural commodities in order to achieve a stronger economic growth that will be stabilized by an increasing foreign exchange reserve. More specifically, countries with low foreign exchange reserves should seek to create a substitute financial system such as national insurance deposits system or sovereign funds that would counterbalance any harmful effect of global financial crisis on their economies.
Thesis(Master) --KDI School:Master of Public Policy,2016